Guiding concepts for park and wilderness stewardship in an era of global environmental change. Issue 9 (2nd December 2009) - Hobbs, Richard J; Cole, David N; Yung, Laurie; Zavaleta, Erika S; Aplet, Gregory H; Chapin, F Stuart; Landres, Peter B; Parsons, David J; Stephenson, Nathan L; White, Peter S; Graber, David M; Higgs, Eric S; et al.
Abstract : The major challenge to stewardship of protected areas is to decide where, when, and how to intervene in physical and biological processes, to conserve what we value in these places. To make such decisions, planners and managers must articulate more clearly the purposes of parks, what is valued, and what needs to be sustained. A key aim for conservation today is the maintenance and restoration of biodiversity, but a broader range of values are also likely to be considered important, including ecological integrity, resilience, historical fidelity (ie the ecosystem appears and functions much as it did in the past), and autonomy of nature. Until recently, the concept of "naturalness" was the guiding principle when making conservation‐related decisions in park and wilderness ecosystems. However, this concept is multifaceted and often means different things to different people, including notions of historical fidelity and autonomy from human influence. Achieving the goal of nature conservation intended for such areas requires a clear articulation of management objectives, which must be geared to the realities of the rapid environmental changes currently underway. We advocate a pluralistic approach that incorporates a suite of guiding principles, including historical fidelity, autonomy of nature, ecological integrity, and resilience, as well as managing with humility. The relative importance of these guiding principles will vary, depending on management goals and ecological conditions.